Т-regulatory cells in atopic dermatitis immune response - D. S. Gonsorunova; L. M. Ogorodova; O. S. Fyodorova; Ye. M. Kamaltynova; Ye. G. Belonogova; Ye. E. Kremer (Бюллетень сибирской медицины, 2011)
Atopic dermatitis — is a chronic disease, with immune mechanisms leading to high level of immunoglobulin Е and abnormal skin reactivity. The current review is presenting the experimental and clinical study results regarding to Т-regulatory cells participation in atopic dermatitis immune response.